2015
DOI: 10.3109/0284186x.2015.1074281
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of first degree family history of breast cancer in young women: Recurrences and bilateral breast cancer

Abstract: Background. The aim of this study is to analyze the impact of first degree relative (FDR) of young breast cancer patients. Methods. Data were used from our prospective population-based cohort study which started in 1983. The family history (FH) was registered with regard to FDR: the presence or absence of invasive breast cancer in none vs. one or more FDRs at any age. Results. A total of 1109 women, 50 years with 1128 breast conserving treatments was seen. The incidence of FDR was 17.0% for one FDR and 3.2% 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A study incorporating Utah's Population Database found that women under the age of 50 with a family history of BC were statistically significantly at a greater risk of a poorer survival when compared to those women without; with a relative risk of 1.54 (95% CI: 0.98–2.41) for women with first degree relatives previously diagnosed with BC . In contrast, a recent population‐based study based in Netherlands reported a lower risk of all‐cause death with ≥2 first‐degree relative with family history (HR 0.2; 95% CI 0.06–1.0). Nevertheless, several studies have found no association between family history and BC overall survival .…”
Section: Discussionmentioning
confidence: 99%
“…A study incorporating Utah's Population Database found that women under the age of 50 with a family history of BC were statistically significantly at a greater risk of a poorer survival when compared to those women without; with a relative risk of 1.54 (95% CI: 0.98–2.41) for women with first degree relatives previously diagnosed with BC . In contrast, a recent population‐based study based in Netherlands reported a lower risk of all‐cause death with ≥2 first‐degree relative with family history (HR 0.2; 95% CI 0.06–1.0). Nevertheless, several studies have found no association between family history and BC overall survival .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, majority of studies focused on the risk factors for the formation of contralateral breast cancer (CBC) in patients with primary breast cancer (PBC) ( 5 ) and expected to prevent the occurrence of CBC via bilateral mastectomy ( 6 , 7 ), whereas, for clinical practice, it is not yet clear whether patients would benefit from bilateral mastectomy in terms of mortality ( 6 ). More importantly, once diagnosed as CBC, how to develop overall treatment strategies and evaluate the prognosis of these MBBC remains confused in clinical ( 8 – 11 ). Actually, most clinical understanding of MBBC is obviously distinct from unilateral breast cancer (UBC) ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…While for clinical practice, it is not yet clear whether patients would benefit from bilateral mastectomy in terms of mortality (5). More importantly, once diagnosed as CBC, how to develop overall treatment strategies and evaluate the prognosis of these MBBC remains confused in clinical (7)(8)(9)(10)32). Actually, most clinical understanding of MBBC is obviously distinct from unilateral breast cancer (UBC) (11,12), and it is urgently needed to build an evaluation model for predicting the prognosis of MBBC.…”
Section: Introductionmentioning
confidence: 99%